Hereditary multiple exostoses in a 13-year-old male: A case report - Nepal, Sarbin; Marahatta, Achyut; Shrestha, Sagun; Bhandari, Shishir (Journal of Chitwan Medical College, 2025)
Hereditary multiple exostoses is a rare autosomal dominant skeletal disorder with multiple cartilage capped benign exostoses occurring at metaphysis of long bones. A 13 years old male presented with multiple nodular lesions in body especially along long bones and was diagnosed as a case of hereditary multiple exostoses (HME) based on clinical picture and x-ray findings and was managed symptomatically. Depending upon the site, number and size of the osteochondromas it can produce variety of clinical features. Having HME increases the risk for developing carcinoma later in life with development of chondrosarcoma more frequently than osteosarcoma. Patient with HME requires special care. While smaller lesions are left untreated and managed symptotically, larger and symptomatic ones may require surgical excision.